Transcriptome Profiling of the Elongating Internode of Cotton (Gossypium hirsutum L.) Seedlings in Response to Mepiquat Chloride - Wang, Li; Yin, Ying; Wang, Li-Feng; Wang, Menglei; Zhao, Miao; Tian, Ye; Li, Yong-Fang (Frontiers in Plant Science, 2020)
The plant growth retardant mepiquat chloride (MC) has been extensively used to produce compact plant canopies and increase yield in cotton (Gossypium hirsutum L.). Previous studies showed that MC reduced plant height and internode length by inhibiting GA biosynthesis and cell elongation. However, whether there are other molecular mechanism underlying MC-induced growth retardation has remained largely unknown. In the present study, we conducted histological, transcriptomic, and phytohormone analyses of the second elongating internodes of cotton seedlings treated with MC. Histological analysis revealed that the MC shortened the internodes through suppressing both cell division and cell elongation. Consistent with the observed phenotype, many genes related to cell growth were significantly downregulated by MC. Transcriptome profiling showed that the expression of genes related not only to GA, but also to auxin, brassinosteroid (BR), and ethylene metabolism and signaling was remarkably suppressed, whereas that of genes related to cytokinin (CTK) and abscisic acid (ABA) metabolism was induced by MC. Consistent with the expression pattern, significant decrease of endogenous GA, auxin, and BR content, but an increase in CTK content was observed after MC treatment. Most of these hormone related genes displayed opposite regulation pattern by exogenous GA3 treatment compared to MC; simultaneous application of MC and GA3 could alleviate the genes expression changes induced by MC treatment, indicating MC does not directly affect other plant hormones, but through the inhibition of the GA biosynthesis. In addition, the expression of genes related to secondary metabolism and many transcription factors (TFs) were differentially regulated by MC. In summary, we confirmed the important role of GA in MC-induced growth inhibition of cotton, and further found that other hormones were also involved in this process in a GA-dependent manner. This study provides novel insights into the molecular mechanism underlying the MC-mediated inhibition of internode elongation in cotton seedlings.